PENGARUH BERMAIN MEDIA PASIR TERHADAP KREATIVITAS PADA ANAK DI KELOMPOK B TK NEGERI PEMBINA 2 PALEMBANG - Sri Wahyuni; yetty rahelly; syafdaningsih syafar (FKIP Universitas sriwijaya, 2017)
Pre-Experimental Research with One Shoot Case Study design entitled Influence Playing Sand Media Against Creativity In Children in Group B TK Negeri Pembina 2 Palembang, have a purpose to know influence of play sand media to creativity in child. Sampling technique used is purposive sampling with low creativity consideration in class B2. Sample amounted to 21 children. Treatment was done 4 times and each posttest was done. Posttest uses a tool in the form of an observation sheet displayed in the form of a test score and converted into a value consisting of 4 indicators. The value of each posttest summed by 4 obtained an average value of 79.23. As the hypothesized data is the data contained in the lower boundary class interval of BSH category value is 63. From the data analysis obtained value tct = 5.20 ? ttable value = 1.72 with 5% significant level and dk = (20) so that concluded there is influence of play sand media on creativity in children in group B TK Negeri Pembina 2 Palembang. This can be seen from every meeting, 3 of the 4 dominant indicators emerge namely, the smooth thinking, flexibility of thinking, and authenticity of thinking. While one indicator that is less emerging is the ability of elaboration of children. It is expected that in the next lesson, more elaboration indicators are trained in making artworks in accordance with their creativity